The Influence of Transformational Leadership Style in Improving The Motivation and Performance of Employees of Perumda Pasar Juara Bandung City - Ferlino, Ricky; Mulyasana, dedi; Indah, Diani (Yayasan Pendidikan Belajar Berdikari, 2025)
Human resources have an important role both in terms of ability and performance in achieving company goals, especially in the Pasar Juara Regional Public Company in Bandung City. In this study, the author uses a quantitative descriptive analysis study method. The quantitative analysis used is a multiple linear statistical model using independent variables and dependent variables. In this study, there are 3 (three) variables used by the author, consisting of 2 (two) independent variables in this case